Effect of Mixed Ratios of Turbinaria murayana Seaweed Meal and Tuna Fish Waste Meal as a Protein Source in Poultry Feed - Reski, Sepri; Mahata, Maria Endo; Rizal, Yose; Dewi, Yelsi Listiana (Andalasian Livestock, 2025)
This study evaluated the effect of different mixing ratios of Turbinaria murayana seaweed meal and tuna fish waste meal as alternative protein sources in poultry feed. The research was conducted using an experimental method arranged in a completely randomised design (CRD) with five treatments and four replications. The treatments consisted of different mixing ratios of Turbinaria murayana seaweed meal and tuna fish waste meal, namely 95:5%, 90:10%, 85:15%, 80:20%, and 75:25%. Data were analysed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test to determine significant differences among treatments. The results showed that varying the mixing ratios had no significant effect (P>0.05) on moisture content, organic matter, crude fiber, crude fat, and calcium levels, but significantly affected (P<0.05) crude protein and phosphorus contents. The 85:15% mixture produced the best nutritional composition as a protein source for poultry feed, with the following nutrient contents: moisture 6.73%, organic matter 82.33%, crude fiber 8.58%, crude protein 31.11%, crude fat 15.35%, calcium 4.10%, and phosphorus 0.30%.